2014
DOI: 10.1007/s00299-014-1670-z
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression of Arabidopsis C-repeat binding factor 3 (AtCBF3) and cold-regulated 15A (AtCOR15A) enhanced chilling tolerance in transgenic eggplant (Solanum melongena L.)

Abstract: Our study shows that the expression of AtCBF3 and AtCOR15A improved the chilling tolerance in transgenic eggplant. In an attempt to improve chilling tolerance of eggplant (Solanum melongena L) plants, Arabidopsis C-repeat binding factor 3 (AtCBF3) and cold-regulated 15A (AtCOR15A) genes both driven by an Arabidopsis RESPONSIVE TO DESSICATION 29A promoter (AtRD29A) were transferred into the plants of eggplant cultivar Sanyueqie. Two independent homozygous transgenic lines were tested for their cold tolerance. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…A previous study indicated that heterologous expression of Arabidopsis CBF3 and COR15A enhanced chilling tolerance in transgenic eggplant (Wan et al . ). In this study, overexpression of SmICE1a in transgenic Arabidopsis results in activation of cold‐responsive genes and an increase in freezing tolerance.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…A previous study indicated that heterologous expression of Arabidopsis CBF3 and COR15A enhanced chilling tolerance in transgenic eggplant (Wan et al . ). In this study, overexpression of SmICE1a in transgenic Arabidopsis results in activation of cold‐responsive genes and an increase in freezing tolerance.…”
Section: Discussionmentioning
confidence: 97%
“…Overexpression of AtCBF3 or AtCBF1 enhanced cold tolerance in transgenic eggplant (Wan et al . ), potato (Pino et al . ) and petunia (Walworth et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Massive studies had revealed that expression of COR genes was positively related to cold tolerance in plants (Liang et al, 2011;Wathugala et al, 2011;Wan et al, 2014). The Cor413 family were divided into Cor413-inner membrane (Cor413im) and Cor413-plasma membrane (Cor413pm) proteins (Ghislain et al, 2003).…”
Section: Discussionmentioning
confidence: 99%